PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN IPAS MATERI BUNYI DAN SIFATNYA UNTUK KELAS V SDN 09 SITIUNG - Yulia Darniyanti; Muhammad Subhan; Dini Puspita Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The background to this research is that students are less interested in participating in the science and science learning process because teachers only use LKPD that are already in the book and many students think that learning science and science is boring learning. Students find it difficult to understand the learning material because the material contained in the LKPD is too short and during the learning process students often go in and out of class and do not focus on listening to the teacher in explaining the material in class. The type of research used is R&D development research (Research & Development). The development method used is the ADDIE development model which consists of five stages of analysis, design, development, implementation and evaluation. The type of data used in this research is qualitative and quantitative data. The data collection techniques used by researchers are interview techniques, observation and documentation. The data analysis technique in this research is in the form of validity, effectiveness and practicality analysis. The results of the assessment of Student Worksheets (LKPD) in science and science learning were tested by three expert validators who obtained an average validity score of 87.25 in the very valid category, a practicality score with an average of 93.4 in the very practical category. Meanwhile, the effectiveness results have an average value of 95 in the very effective category. So it can be concluded that the Student Worksheet (LKPD) Based on Problem Based Learning (PBL) in Science and Science Learning Sound Material and Its Properties for Class V SDN 09 Sitiung can be used in the learning process